The Influence of Servqual Dimensions on Customer Satisfaction and Repeat Order Decision in Financing Companies - Shinta Yunita; Juhaini Alie (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study aims to analyze the effects of service quality comprising the dimensions of tangibles, empathy, and responsiveness on customer satisfaction and decisions (repeat orders) at PT Mandiri Tunas Finance. Service quality is a critical factor in building customer loyalty, particularly within the highly competitive financing industry. This research adopts a quantitative approach using a survey method involving 150 customers of PT Mandiri Tunas Finance. The data were analyzed using Structural Equation Modeling (SEM) with the SmartPLS software to examine both partial and simultaneous effects among the research variables. The results indicate that the dimensions of tangibles, empathy, and responsiveness have positive and significant effects on customer satisfaction, with empathy exerting the strongest influence. Furthermore, customer satisfaction has a significant effect on repeat order decisions. Collectively, the service quality variables explain 51% of the variance in customers’ repeat order decisions. The findings underscore the importance of integrated service quality management in enhancing customer satisfaction and loyalty. Practically, the results suggest the need to improve physical facilities, including the utilization of technology, to strengthen empathy-based training for service staff, and to optimize service responsiveness. These efforts are expected to enhance customer satisfaction and, ultimately, increase repeat order (repeat order) behavior.